Intra-mitochondrial biomineralization for inducing apoptosis of cancer cells. Issue 9 (6th February 2018) - Kim, Sangpil; Palanikumar, L.; Choi, Huyeon; Jeena, M. T.; Kim, Chaekyu; Ryu, Ja-Hyoung
Abstract : Mitochondria targeting mineralization can form biominerals inside cancerous mitochondria through concentration dependent silicification, resulting in dysfunction of mitochondria leading to apoptosis. These results suggest potential therapeutics for cancer treatment. Abstract : The use of biomineralization that regulates cellular functions has emerged as a potential therapeutic tool. However, the lack of selectivity still limits its therapeutic efficacy. Here, we report a subcellular-targeting biomineralization system featuring a triphenylphosphonium cation (TPP) (the mitochondria-targeting moiety) and trialkoxysilane (the biomineralization moiety via silicification). The TPP-containing trialkoxysilane exhibited approximately seven times greater cellular uptake into cancer cells (SCC7) than into normal cells (HEK293T) due to the more negative mitochondrial membrane potentials of the cancer cells. In turn, its accumulation inside mitochondria (pH 8) induces specific silicification, leading to the formation of silica particles in the mitochondrial matrix and further activation of apoptosis. In vivo assessment confirmed that the biomineralization system efficiently inhibits tumor growth in a mouse xenograft cancer model. Exploiting both the subcellular specificity and the targeting strategy provides new insight into the use of intracellular biomineralization for targeted cancer therapy.